Values stories for Filipino children - Reyes, Fe Aida Lacsamana; Quimpo, Vergilio (Pasig City Anvil, 2007)
"Hopefully this book, through its values-laden stories and activities, will help children gain self-confidence and belief in their innate goodness. Most of the stories here are true or have roots in my childhood in Davao. In reading these stories, I hope that the readers will be motivated to write and share their own stories or read similar ones from other sources."--Preface.
The boy and his kite -- The butterfly -- The man in the rice field -- The best swimmer -- The shoeshine boy -- Tukkoo! -- Fishes by the rocks -- The twins -- The firewood gatherers -- Rico, the banana boy -- Sampaguitas -- Saved by the dolphins.
Illustrations by Vergilio Quimpo.
Keywords: Moral education -- Philippines; Values in literature; Values -- Study and teaching (Elementary) -- Activity programs; Values -- Philippines; Children's stories, Philippine; Children -- Conduct of life